Beyond academics - is community engagement possible through work integrated learning? - Budd, Jean (School of Education, 2016)
The purpose of this study was to investigate whether two work integrated learning modules were the appropriate means to achieve community engagement ends, and to what extent the introduction of an NGO component in the WIL curriculum raised awareness or understanding of community engagement amongst the students at a private higher educational institution. Theoretical fields that guided the research included community engagement studies by Butin(2010) and Lazarus (2008), experiential learning literature encompassing work integrated learning, and the literature on service learning and transformative learning with a particular focus on Kolb's (1984) experiential learning cycle and the important role of critical reflection. This was a single case study conducted at a private higher education institution, which employed qualitative research methodology to analyse two work integrated learning modules. McCowan's (2008) curricular transposition framework was used to analyse whether the community engagement ideal was realised, and to identify any disjunctures that inhibited its implementation and realisation. To accomplish this four groups of participants were interviewed, each representing a different stage in McCowan's model. These were curriculum developers, work integrated learning lecturers, students from each work integrated learning module and a representative from the chosen NGO. From their perspectives key themes emerged revolving around levels of conviction of all stakeholders, forms of learning and degrees of student transformation. All of these indicated disjunctures between the "ideal" and what was actually achieved, and these acted as constraining factors which affected the transposition from ideal to real. My data suggests that WIL modules can be an appropriate means to achieve community engagement ends, but the "ideal" needs to have the support of all stakeholders and should be embedded firmly in the curriculum. The data also shows that because of the lack of conviction on the part of all stakeholders the community engagement awareness or understanding happened almost implicitly, as part of the hidden curriculum. Additionally, even though some awareness of community engagement did occur for students, the superficiality of the NGO engagement provided a superficial student experience. The evidence points to the conclusion that the use of work integrated learning modules as a means to promote community engagement awareness was moderately successful, but a lot more needs to be done to make it a viable and worthwhile option. Belief in the concept, clarity on goals and objectives, proper training and development of lecturers, constructive feedback loops, more intensive NGO engagement and support from all stakeholders involved are issues that need to be addressed to move towards realisation of the "ideal".